Earnings management, audit quality, and cost of debt: evidence from a Central Asian economy. Issue 6 (13th June 2019) - Orazalin, Nurlan; Akhmetzhanov, Rassul
Abstract : Purpose: This study aims to examine the effects of earnings management and audit quality on cost of debt of listed companies in Kazakhstan. The study also investigates the effects of audit quality on earnings management and whether the relationship between earnings management and cost of debt is affected by audit quality in the context of a given emerging economy. Design/methodology/approach: The study sample consists of public companies listed in the Kazakhstan Stock Exchange (KASE) from 2011 to 2016, and all data were obtained from audited financial statements and annual reports downloaded from the webpage of KASE. The study uses the cross-sectional ordinary least squares technique to test the impact of audit quality and earnings management on cost of debt. Findings: The collected empirical evidence shows that earnings management is negatively related to cost of debt. The findings also indicate that higher audit quality leads to a lower cost of debt. However, the results suggest that audit quality has no impact on earnings management and that the effect of earnings management on cost of debt is not different for the companies audited by the Big Four and for the companies audited by other audit firms. Practical implications: The findings of the study can be of interest to policy-makers, regulators, investors and practitioners in emerging markets with an institutional environment similar to that of Kazakhstan. Originality/value: The study throws more light on the impact of earnings management and audit quality on cost of debt in Kazakhstan, representing the Central Asian region. This study also extends the current literature by providing empirical evidence that the relationship between earnings management and cost of debt is not affected by audit quality.